Respuesta :
Answer:
The expressions are not equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(2)-6=-30
Step-by-step explanation:
Two expressions are said to be equal if after a number is substituted to the expression, they produce the same result (that is they have the same value).
To determine whether -3x(5-4)+3(x-6) is equivalent to -12x-6, we have to substitute the same number to the expression and see if it produces the same result.
Substituting 2 to the first expression gives:
-3×2(5-4) + 3(2 - 6) = -6 - 12 = -18
Substituting 2 to the second expression gives:
-12(2) - 6 = -24 - 6 = -30
Since -3×2(5-4) + 3(2 - 6) = -6 - 12 = -18 and -12(2) - 6 = -24 - 6 = -30, the expressions are not equivalent because they do not produce the same result.
The correct procedure that justifies their equality is the expressions are equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(1)-6=-18
Expressions and values
Equations are written by equating two expressions
Given the following equation -3x(5-4)+3(x-6)
Expand
-15x + 12 + 3x - 18
Collect the like terms
-15x + 3x + 12 - 18
-12x - 6
Hence the correct procedure that justifies their equality is the expressions are equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(1)-6=-18
Learn more on equations here: https://brainly.com/question/2972832
#SPJ5